5x-3-30=4x-3+6x

Simple and best practice solution for 5x-3-30=4x-3+6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-3-30=4x-3+6x equation:


Simplifying
5x + -3 + -30 = 4x + -3 + 6x

Reorder the terms:
-3 + -30 + 5x = 4x + -3 + 6x

Combine like terms: -3 + -30 = -33
-33 + 5x = 4x + -3 + 6x

Reorder the terms:
-33 + 5x = -3 + 4x + 6x

Combine like terms: 4x + 6x = 10x
-33 + 5x = -3 + 10x

Solving
-33 + 5x = -3 + 10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10x' to each side of the equation.
-33 + 5x + -10x = -3 + 10x + -10x

Combine like terms: 5x + -10x = -5x
-33 + -5x = -3 + 10x + -10x

Combine like terms: 10x + -10x = 0
-33 + -5x = -3 + 0
-33 + -5x = -3

Add '33' to each side of the equation.
-33 + 33 + -5x = -3 + 33

Combine like terms: -33 + 33 = 0
0 + -5x = -3 + 33
-5x = -3 + 33

Combine like terms: -3 + 33 = 30
-5x = 30

Divide each side by '-5'.
x = -6

Simplifying
x = -6

See similar equations:

| (-7a^2b^3c^0)/(3a^2b^4c^3)^-4 | | 27-2x=20-8x | | 32m=2496 | | -152=-8(6x+1) | | 5x+11=5x-17 | | 4y+(-2)=34 | | 22=-3(5k+6) | | 5x+11=-8x-17 | | 8x-27+146=180 | | Y=-x+250 | | 7x+13=7x-18 | | 2-8(1-9n)=28 | | 7x+13=-8x-18 | | 13p=546 | | 0=m-5-6m | | -y(dx)+(x+sqrt(xy))(dy)=0 | | 8x-27+29=180 | | 3(5a-6)=21+9a | | 7x+13=-5x-16 | | 24*(1+x)=49 | | 100t=120t | | -2y=-108 | | 3x=120t | | 4(6-5b)=35 | | 3(2x)1=25 | | 3/y-1=2-7/y-1 | | 5(-2x+4)-7=3x+52 | | n*8=7 | | 10=A/-7 | | Y=2+-2+10 | | 4(x+6)=4(x+14) | | 8w^3+14w^2+3w=0 |

Equations solver categories